Be better or merry how mood affects self-control. [article]. - Fishbach, Ayelet
In 6 studies, the authors tested whether the effect of mood on self-control success depends on a person's accessible goal. We propose that positive mood signals a person to adopt an accessible goal, whereas negative mood signals a person to reject an accessible goal; therefore. if a self-improvement goal is accessible, happy (vs. neutral or unhappy) people perform better on self-control task that further that goal. Conversely, if a mood management goal is accessible, happy people abstain from self-control tasks because the tasks are incompatible with this goal. This pattern receives consistent support across several self-control tasks, including donating to charity, demonstrating physical endurance, seeking negative feedback, and completing tests. -- (from the author)
Keywords: Self-contol.; Self-regulation.; Mood; Accessibility; Goals